2015
DOI: 10.1063/1.4931810
|View full text |Cite
|
Sign up to set email alerts
|

Existence of the β-tin structure in Sr: First evidence from computational approach

Abstract: Molecular Dynamics (MD) calculation is one of the most powerful theoretical methods widely used to predict and to confirm structural phase transitions. In this work, the MD method has been used to verify phase transition from body-centered cubic (bcc) to β-tin structure, then, to the Cmcm and hexagonal close-packed (hcp) structure, respectively. The transition sequence from previous theoretical works has been confirmed. In this study, Density Functional Theory (DFT), has been used to calculate phonon dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The structural phase transitions in AEMs have been previously investigated. A theoretical study of Sr, [ 10 ] as indicated by the screened exchange local density approximation, was able to predict the transition nature of Sr and in turn reported agreement with experimental observations. Moreover, the structures in AEMs can be attributed to the possibility of being able to examine the stable structure through the energy of valence states.…”
Section: Introductionmentioning
confidence: 58%
“…The structural phase transitions in AEMs have been previously investigated. A theoretical study of Sr, [ 10 ] as indicated by the screened exchange local density approximation, was able to predict the transition nature of Sr and in turn reported agreement with experimental observations. Moreover, the structures in AEMs can be attributed to the possibility of being able to examine the stable structure through the energy of valence states.…”
Section: Introductionmentioning
confidence: 58%
“…It should be noted that our calculations were performed at a temperature of 0 K, indicating that the enthalpy can confirm a phase stability under high pressure. [30,31,32,33,34,35,36,37] This is due to the fact that there is no entropy contribution. As a result, the relationship between pure elements Hf and O displayed the formation of HfO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For further details of the energy cutoff for plane waves and the Monkhorst-Pack k-point mesh as well as the DFT software have been described extensively in Refs. [10,[12][13][14]. Our works used the AIRSS technique, based on the density functional theory, to predict the novel structure.…”
Section: Methodsmentioning
confidence: 99%
“…However, the discrepancy between the experimental observations and the theoretical studies were not solved yet. In 2015, the discrepancies in transition sequence between the experimental and theoretical works was explained by Tsuppayakornaek et al [10]. Regarding transition sequence in Sr., it was investigated by the hybrid exchange-correlation functional, i.e.…”
Section: Strontiummentioning
confidence: 98%
See 1 more Smart Citation